Emotional Geography of Non-English Department Students on Extensive Reading - Areta Puspa (Abjadia, 2022)
This present study is aimed to investigate the students feeling when they are asked for extensive reading, in case of reading news. The non-English department students who take English course are involved as the participants. The data were gathered from students’ emotion diaries and interviews. Data were analysed by a constant comparative method. The salient points that emerge from the data are positive and negative emotions elaborating into four forms of emotions, namely (1) attention, (2) motivation, (3) use of learning strategies, and (4) self-regulation of learning. The implication of this present study is a mapping of students feeling for non-English departments on extensive reading